Enacting toxicity: epidemiology and the study of air pollution for public health. Issue 3 (27th May 2017) - Garnett, Emma
Abstract: This paper presents air pollution as a 'post-human' public health phenomenon. It draws on an ethnography of a multidisciplinary research project called Weather Health and Air Pollution to explore the material ways in which air pollution challenged scientists' conceptualisations of harm and health. The epidemiologists on WHAP used statistical techniques to correlate data of air pollution concentrations with mortality and morbidity data collected by hospitals in order to establish a quantified measure of the health effects of exposure to air pollution. Initially, these correlations were problematic: plotted data points failed to map over temporal patterns. A series of negotiations followed. As a result of these, the concept of 'season' emerged as a temporal figure through which the very existence and meaning of air pollution was put to the test. Indeed, attempts by researchers to hold stable the notion of toxicity signalled the problem of trying to assess the bodily response to a polluted environment that has supposedly 'already been'. The paper concludes by arguing how contemplating health through the lens of the material dimensions of time allows public health to: first, view health problems as constituted through bodies and environments, rather than as a relation separating the two; and second, open up indeterminacies and uncertainties as a generative condition of air pollution, and perhaps public health more generally.